Ischemia preconditioning induces an adaptive response that defines a circulating metabolomic signature in ischemic stroke patients. Issue 12 (December 2022) - Sol, Joaquim; Colàs-Campàs, Laura; Mauri-Capdevila, Gerard; Molina-Seguin, Jessica; Galo-Licona, José Daniel; Torres-Querol, Coral; Aymerich, Núria; Ois, Ángel; Roquer, Jaume; Tur, Silvia; García-Carreira, María del Carmen; Martí-Fàbregas, Joan; et al.
Transient ischemic attacks (TIAs) before an acute ischemic stroke (AIS) could induce ischemic tolerance (IT) phenomena. with an endogenous neuroprotective role (Ischemic preconditioning. IPC). A consecutive prospective cohort of patients with AIS were recruited from 8 different hospitals. Participants were classified by those with non-previous recent TIA vs. previous TIA (within seven days. TIA ≤7d). A total of 541 AIS patients were recruited. 40 (7.4%). of them had previous TIA ≤7d. In line with IPC. patients with TIA ≤7d showed: 1) a significantly less severe stroke at admission by NIHSS score. 2) a better outcome at 7–90 days follow-up and reduced infarct volumes. 3) a specific upregulated metabolomics/lipidomic profile composed of diverse lipid categories. Effectively. IPC activates an additional adaptive response on increasing circulation levels of structural and bioactive lipids to facilitate functional recovery after AIS which may support biochemical machinery for neuronal survival. Furthermore. previous TIA before AIS seems to facilitate the production of anti-inflammatory mediators that contribute to a better immune response. Thus. the IT phenomena contributes to a better adaptation of further ischemia. Our study provides first-time evidence of a metabolomics/lipidomic signature related to the development of stroke tolerance in AIS patients induced by recent TIA.